Robinsons Children's Library, Inc.-Imus, Cavite provider of library services to children - Cruz, Fraymon Joy P.; Dela Torre, Nathalie N. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This study assessed the case of Robinsons Children's Library, Inc. (RCLI)-Imus RCLI as provider of services to children. The general purpose fo this study was to assess the RCLI-Imus, Cavite as provider of services to children with the children as respondents. There are 500 library users of the Children's Library Inc.-Imus Branch who were given the said questionnaires. All of them returned the questionnaires. This is equivalent to 100 percent of the sample population.
Results of the study revealed that the RCLI (Imus, Cavite Branch) was effective in achieving its goals, mission, and vision. This is best supported by the overwhelming satisfaction rate given by the respondents of RCLI (Imus, Cavite Branch). The head librarian fully accomplishes his/her duties and responsibilities to the library users by providing the different services offered by the library. The library staff and the library users have a smooth relationship with one another when it comes to library services and activities offered by the RCLI. Thus, the mission for which it was established is accompanied by the RCLI.
Based on the conclusions of the study, the researcher recommends the following: a) The head librarian and the staff of the RCLI-Imus, Cavite Branch need to continue doing their tasks in giving library services to different users of the Children's Library. They need to try all types of communications to be able to inform the other children who do not know the existence of the RCLI; b) The head librarian needs to meet the different heads of the nearby schools and inform them of the services and programs provided by the RCLI. The information that the heads will be getting will then be re-echoed to their respective subordinates and re-echoed once again to the pupils concerned; c) The library needs to evaluate its collection monthly to assess its efficiency and the satisfaction of its patrons with its services and resources; d) The library needs to look for more volunteer staff who are library science students since they know more about library processes; and e) The staff also needs to attend more seminars to acquire new knowledge.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Robinsons Children's Library, Inc. (RCLI)-Imus.; Children's libraries -- Philippines -- Cavite (Imus).